Anonymous
Anonymous asked in Education & ReferenceHomework Help · 8 years ago

Solve these equations:

2x + 2 = 27 - 3x

3(x - 2) = -2 (2x +3)

2(3 - x) = 4(3 - 2x)

Cheers for the help xox

Update:

3x - 4 = 2

Relevance

2x + 2 = 27 - 3x

First add 3x to both sides of the equation

5x+2=27

then subtract 2 from both sides

5x=25

Lastly, divide by 5 from both sides

x=5

3(x - 2) = -2 (2x +3)

First distribute 3 into (3x-2) and distribute -2 into (2x+3) using the distributive property

3x-6 = -4x-6

Then, add 4x to both sides

7x-6 = -6

Next, add 6 to both sides

7x=0

then divide by 7 to both sides, but it will still equal 0

x=0

2(3 - x) = 4(3 - 2x)

Use the distributive property on both sides of the equation by multiplying the numbers/variables in the parantheses by the number outside the parantheses

6-2x = 12-8x

Next, add 8x to both sides

6+6x = 12

Next subtract 6 to both sides

6x = 6

lastly, divide both sides by 6

x=1

3x-4= 2

First add 4 to both sides

3x= 6

then divide both sides by 3

x= 2

• 1) x=5

2x+2=27-3x first - 2 from both sides

-2x -2x you should get:

2=27-5x then subtract 27 from both sides

-27 -27 you should get

-25=-5x divide both sides by -5

You should get x=5

2) x=0

3(x-2)= -2(2x+3) first distribute (3 to x and 2/ -2 to 2x and 3) you should get:

3x-6=-4x-6 then subtract 3x from both sides

-3x -3x you should get:

-6=-7x-6 then add 6 to both sides

+6 +6 you should then get:

0=-7x so x will equal 0

Now do the same steps with the other two to get these answers:

3) x=1

4) x=2

and for number 3 you will eventually get to

3) 6x=6 so now divide both sides by 6 and you get x=1

do the same for 4